Evaluation of creatine kinase (CK) and aspartate aminotransferase (AST) activities after laparoscopic or conventional ovariectomy in queens - Alves, A. E. [UNESP]; Ribeiro, A. P C [UNESP]; Filippo, P. A. [UNESP]; Apparicio, M. F. [UNESP]; Motheo, T. F. [UNESP]; Mostachio, G. Q. [UNESP]; Vicente, W. R R [UNESP]; Moore, A. Hotston (Gesellschaft Schweizer Tierarztinnen und Tierarzte, 2009)
Creatine kinase (CK) and aspartate aminotransferase (AST) are mainly muscle-specific enzymes, which can be associated with muscle tissue damage. The aim of this study was to assess the activities of CK and AST during the postoperative period, after conventional (G1) and videolaparoscopic ovariectomy (G2), in queens. A further group (G3) was subjected to anaesthesia only. Results demonstrate that there were significant differences between groups. The highest levels of CK were recorded in Gl, however at a confidence level of p < 0.05 there was no significant difference between groups during the first 6 hours after surgery. A significant (p < 0.05) increase of CK values was identified between 0h and 3h in both groups (Gl and G2). Regarding AST activity there was no significant variation between groups, but again there was a significant difference between values at 0h and 3h after surgery. In conclusion, ovariectomy performed by videolap-aroscopy seems to cause less muscle damage when compared to the conventional method. © 2009 by Verlag Hans Huber, Hogrefe AG, Bem.
Keywords: Muscle enzymes; Queen; Videolaparoscopy; aspartate aminotransferase; creatine kinase; animal; animal disease; cat; comparative study; endoscopic surgery; enzymology; female; injury; laparoscopy; metabolism; methodology; ovariectomy; randomization; skeletal muscle; Animals; Aspartate Aminotransferases; Cats; Creatine Kinase; Female; Laparoscopy; Muscle, Skeletal; Ovariectomy; Random Allocation; Video-Assisted Surgery